2007
DOI: 10.1002/jbm.b.30762
|View full text |Cite
|
Sign up to set email alerts
|

Improved bone ingrowth and fixation with a thin calcium phosphate coating intended for complete resorption

Abstract: Bonit is claimed to be a resorbable electrochemically deposited calcium phosphate coating consisting mainly of brushite, which is a hydroxyapatite precursor. This study involved a comparison of Ti6Al4V screw-shaped implants with and without a 15 +/- 5 microm Bonit coating in rabbit tibia and femur, after 6 and 12 weeks of insertion. The biomechanical removal torque test showed significantly increased values for the coated implants after 12 weeks (p < 0.05) but not after 6 weeks of integration. Higher bone-impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 70 publications
(88 reference statements)
3
41
0
Order By: Relevance
“…Furthermore, brushite crystallites are bioactive and support the direct linkage to bone tissue. [18] For MgCPC-filled Fe samples, comparable corrosion behaviour to Fe-B with less released iron and fewer iron oxidation by-products could be observed; high cell proliferation was also observed.…”
Section: Biological Properties and Perspectivesmentioning
confidence: 79%
“…Furthermore, brushite crystallites are bioactive and support the direct linkage to bone tissue. [18] For MgCPC-filled Fe samples, comparable corrosion behaviour to Fe-B with less released iron and fewer iron oxidation by-products could be observed; high cell proliferation was also observed.…”
Section: Biological Properties and Perspectivesmentioning
confidence: 79%
“…In the current study, histomorphometric evaluation was selected because it is a reliable and well-defined method for which considerable work has been performed and numerous historical data are available [6,[8][9][10]. This study demonstrated that polyethylene implants coated with Ti-PVD and biomimetically or electrolytically deposited HA were able to develop osseointegration comparable to that of a plasma sprayed-HA coated titanium PE implant, that are largely used in hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In a rabbit model in which implants were inserted in the cortical bone, the comparison of plasma sprayed HA-coated and electrolytic HA-coated titanium implants showed greater values of ISS for plasma sprayed HAcoated implants at six and 12 weeks but not at 52 weeks where ISS was even significantly lower than for electrolytic HAcoated implants. The authors explained these results by a slower bone bonding associated with a lower rate of fibrosis with electrolytic HA coating [6,11]. Furthermore, it has been also assumed that biomimetic HA deposition could limit the coating delamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further accelerate and enhance bone ingrowth, a thin bioactive calcium phosphate coating can be deposited on the surface of AM porous scaffolds [51] (Fig. 2).…”
Section: Features Of Am Orthopaedic Implantsmentioning
confidence: 99%